Applications and techniques in information security : 6th [i.e. 7th] International Conference, ATIS 2016, Cairns, QLD, Australia, October 26-28, 2016, Proceedings /: 6th [i.e. 7th] International Conference, ATIS 2016, Cairns, QLD, Australia, October 26-28, 2016, Proceedings. (2016) - Unknown
No abstract available